Fungal pneumonia in COVID-19 patients: Risk factors and early prediction - Hala Samaha; Arif Al Nooryani; Sumaya Alzarooni; Hala Ismail; Amina Aljasmi; Samah Allam; Abeer Oraby; Wassan Idris; Khaled Donia; Ahmed Eid (Egyptian Journal of Chest Disease and Tuberculosis, 2023)
Objective To determine the risk factors for developing secondary fungal pneumonia in moderate to severe coronavirus disease 2019 (COVID-19) cases. Using predictors of fungal infection helps to guide the diagnosis and treatment in these cases and save their lives. Patients and methods A total of 257 patients with moderate to severe COVID-19 pneumonia were examined in this retrospective study at Al Qassimi Hospital of EHS. An assessment of clinical, laboratory, and radiologic findings was performed upon admission. The data were collected and analyzed. Results Overall, 32% of critically ill COVID cases had fungal infection; 47% of them were candida, whereas aspergillosis and yeast were positive in 26.5% each. At the time of hospitalization, computed tomography chest findings had a strong correlation with fungal culture results in COVID-19 cases. Fungal infection in COVID-19 cases correlated strongly with metabolic acidosis, high erythrocyte sedimentation rate, high blood sugar, need for mechanical ventilation at admission, vasopressor use, renal replacement, long duration of steroid treatment, long stay in ICU, and long duration on mechanical ventilation. The longer the duration of PCR positivity, the higher the incidence of positive sputum fungal culture result. Conclusion COVID-19-infected patients with other risk factors for fungal infections should always be considered to have fungal infections if pathogenic organisms are isolated from respiratory secretions or other microbiological or immunological markers appear positive. Computed tomography chest finding in COVID-19 cases is an important predictor for fungal infection.